Misconceptions in Solving Remaining Problems of Dividing Exponential Numbers - Setiawan, Yayan Eryk; Abidin, Zainal; Sunismi, S (Universitas Muhammadiyah Surakarta, 2024)
Preliminary research results show that many students still experience errors in determining the remainder of the distribution of exponential numbers. This error is important for further analysis. Therefore, this study aims to identify student errors in determining the remainder of the division of exponential numbers. This type of research is descriptive qualitative research. The subjects of this study consisted of 4 students from the mathematics education study program. The data collected in this study consisted of the results of the subject's work and transcripts of interviews with the subject. Analysis of the results of the subject's work was carried out descriptively to determine the characteristics of the errors. Analysis of the transcripts of the interview results was carried out by coding the words that indicated the causes of misunderstandings. The results showed that the misunderstanding of the concept in determining the remainder of the division of exponential numbers by integers consisted of errors in changing the exponential form into the sum of exponential numbers, errors in translating exponential numbers, errors using modulo congruence, and errors in dividing the sum of exponential numbers. The factor that causes this misunderstanding in general is a lack of understanding of the basics of operations on exponential numbers and modulo properties.